Hif-1α and IGF Expression in Endometrial Hyperplasia - Z. V. Chumak; M. V. Shapoval; O. G. Andrievskiy (Kazimierz Wielki University, 2020)
The objective: to assess the effect of insulin resistance and hypoxia on the risk of endometrial hyperplasia development. The research was conducted on the base of Municipal Maternity House №5 (Odessa, Ukraine). The data obtained from the sample of 417 reproductive, perimenopausal, and postmenopausal age women who referred for medical care to the gynecological department, were analyzed. All the women under examination were carried out medical and diagnostic scraping of the uterine cavity. Results. The intensity of hypoxia increases with age and closely correlates (r=0,78) with the level of insulin resistance. IGF demonstrates reverse dynamics - its rates has been diminished with age (r=-0,63). Conclusion. It was demonstrated that insulin resistance and hypoxia play significant role in the pathogenesis of endometrial hyperplasia. Indices of IGF and HIF could be recommended as valuable biomarkers of prognosis in the case of endometrial hyperplasia.